IMPLEMENTASI METODE UMMI DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SISWA KELAS III B IBNU KHALDUN SD AL-FIRDAUS ISLAMIC SCHOOL SAMARINDA TAHUN PEMBELAJARAN 2015/2016 - Afdal Afdal (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2016)
Al-Qur'an down in Arabic, it is highly recommended us to learning languages, so that we can read, interpret, understand and implement what is stated in the Qur'an. In this study using Ummi in reading the Qur'an. Ummi method focused on three things are concerned, namely: method quality, teacher quality, and systems that prioritize quality. In this study, researchers formulate problems, namely how Implementation Methods Ummi in enhancing the ability to read the Qur'an Grade SD III.B Ibnu Khaldun Al-Firdaus Samarinda Islamic School Year 2015/2016? The purpose of this study was to determine Impementasi Ummi method in elementary Islamic School Al-Firdaus Samarinda and know the increased ability to read the Qur'an class III.B Ibnu Khaldun in Al-Firdaus Islamic Elementary School Samarinda.This study is a qualitative descriptive aimed to describe that are taking place. In other words, a qualitative descriptive study aimed to obtain information about the existing situation. The present study examined children in elementary Islamic School Al- Firdaus Samarinda precisely graders III.B Ibnu Khaldun. The reason of choosing a place in the present study were researchers able to engage in a learning process directly and within a period that is long enough to do the research. So as to facilitate the research process.Based on the results of observations made by researchers that many children who have not been able remember short letters as well as readings and also its short length can not be read even if the letter hijaiyah but less well versed in reading the Qur'an. Meanwhile, after school using methods Ummi in reading the Qur'an post the results of tests conducted by researchers is seen the change between reading and memorizing is done by the students, seen from the analysis, because of the actions carried out by researchers really do ummi method implementation in accordance with what has been in written and explained by experts how to teach the method ummi ummi methods to students. Therefore it can be concluded that by using the method Ummi can improve the ability to read the Qur'an in class III.B Ibnu Khaldun in Al-Firdaus Islamic Elementary School Samarinda and implementation methods in primary Ummi Al-Firdaus Samarinda Islamic School has been running with good.